2003
DOI: 10.1080/09629350310001633360
|View full text |Cite
|
Sign up to set email alerts
|

Levels of serum IL‐1β, IL‐2, IL‐8 and tumor necrosis factor‐α in patients with unstable angina pectoris

Abstract: We detected high levels of IL-1beta, IL-8 and TNF-alpha in patients with UAP during early phase. We suggest that proinflammatory cytokines (e.g. IL-1beta,IL-8, TNF-alpha) may play an important role in the development of atherosclerosis and its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 24 publications
1
38
0
1
Order By: Relevance
“…TNF-alpha also upregulates membrane expression of vascular cell adhesion molecule-1 [56], which plays a well established role in atherosclerosis [57] and it precedes the development of thickened intima with foam cell lesions [58]. Apart from these in vitro observations, increased expression of serum TNF-alpha has been found in patients with atherosclerotic complications in population studies [59,60]. In RA patients, TNF-alpha enhances prothrombotic states such as dyslipidemia [61], but, most importantly, pooled evidence reveals that anti-TNF-alpha treatment may be in part responsible for reducing the risk for CVD events in RA [62].…”
Section: Inflammation and Atherosclerosismentioning
confidence: 97%
“…TNF-alpha also upregulates membrane expression of vascular cell adhesion molecule-1 [56], which plays a well established role in atherosclerosis [57] and it precedes the development of thickened intima with foam cell lesions [58]. Apart from these in vitro observations, increased expression of serum TNF-alpha has been found in patients with atherosclerotic complications in population studies [59,60]. In RA patients, TNF-alpha enhances prothrombotic states such as dyslipidemia [61], but, most importantly, pooled evidence reveals that anti-TNF-alpha treatment may be in part responsible for reducing the risk for CVD events in RA [62].…”
Section: Inflammation and Atherosclerosismentioning
confidence: 97%
“…High levels of IL-1 b, IL-8, and TNFa in patients with unstable angina pectoris suggested that these proinflammatory cytokines play an important role in the development of atherosclerosis and its complications (Ozeren et al, 2003). Studies of human myoblasts and isolated muscle tissue showed combinatorial effect of IL-1 b and IL-17 on the production of factors involved in inflammation (Chevrel et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Among genes downregulated at 1 day and 3 days posttransplantation in CsA 1 peptide treatment were proinflammatory cytokines such as Interleukin-1 beta (IL-1 b), the members of their receptor complexes (IL1r2, IL1nr), and cell adhesion molecules involved in the leukocyte adhesion cascade such as Selectin (Arstall et al, 1999;Batten et al, 1996;Bick et al, 1997;Chevrel et al, 2002;Finesterer, 2009;Ing et al, 1999;Kacimi et al, 1998;Li and Xiao, 2001;Libby et al, 1988;Libby, 1989, 1990;Loppnow et al, 1998;Long, 2001;Mountain et al, 2008;Muller-Werdan et al, 1998;Ono et al, 1998;Ozeren et al, 2003;Tomita et al, 2004;Ukimura et al, 2003;Westphal et al, 2008;Xia et al, 2006) (Table 2 and Fig. 2).…”
Section: Genes Downregulated In Csa 1 Peptide Treatmentmentioning
confidence: 97%
“…was found in human atherosclerotic plaques [1,11]. The concentrations of MCP-1, IL-8, IL-2 receptor soluble α-subunit (sCD25), IL-6, IL-1β, and other proinfl ammatory markers are elevated in the blood of patients with unstable angina [2,8,13]. High levels of highly sensitive C-reactive protein (hsCRP) and MCP-1 are independent risk factors for repeated cardiovascular events in patients with a history of acute coronary syndrome (ACS) [5].…”
mentioning
confidence: 99%